Concrete drawing: intra-active potentials in drawing, objects and urbanity - Twose, Simon (Interstices: Journal of Architecture and Related Arts, 2015)
In designing built space, a series of material engagements impress themselves on the process; desires and hopes find shape in the virtual forming of space, and in this drawing, or drawing out, the implacable scale and substance of building has ambiguous presence. This paper discusses the Concrete drawing, a work that hovers between building and drawing, as a lens to re-orient thinking on objects, buildings and the city. Various intra-actions between drawing, building and occupation are expanded upon, using the Concrete drawing as an armature for discussion. The work problematises as much as concludes, but points to how designing and urbanity might impress on one another, with the city having the restless potentiality of drawing.